Absence of the cbb(3) Terminal Oxidase Reveals an Active Oxygen-Dependent Cyclase Involved in Bacteriochlorophyll Biosynthesis in Rhodobacter sphaeroides - Chen, Guangyu E. (J Bacteriol, 2016)
The characteristic green color associated with chlorophyll pigments results from the formation of an isocyclic fifth ring on the tetrapyrrole macrocycle during the biosynthesis of these important molecules. This reaction is catalyzed by two unrelated cyclase enzymes employing different chemistries. Oxygenic phototrophs such as plants and cyanobacteria utilize an oxygen-dependent enzyme, the major component of which is a diiron protein named AcsF, while BchE, an oxygen-sensitive [4Fe-4S] cluster protein, dominates in phototrophs inhabiting anoxic environments, such as the purple phototrophic bacterium Rhodobacter sphaeroides. We identify a potential acsF in this organism and assay for activity of the encoded protein in a strain lacking bchE under various aeration regimes. Initially, cells lacking bchE did not demonstrate AcsF activity under any condition tested. However, on removal of a gene encoding a subunit of the cbb(3)-type respiratory terminal oxidase, cells cultured under regimes ranging from oxic to micro-oxic exhibited cyclase activity, confirming the activity of the oxygen-dependent enzyme in this model organism. Potential reasons for the utilization of an oxygen-dependent enzyme in anoxygenic phototrophs are discussed. IMPORTANCE The formation of the E ring of bacteriochlorophyll pigments is the least well characterized step in their biosynthesis, remaining enigmatic for over 60 years. Two unrelated enzymes catalyze this cyclization step; O(2)-dependent and O(2)-independent forms dominate in oxygenic and anoxygenic phototrophs, respectively. We uncover the activity of an O(2)-dependent enzyme in the anoxygenic purple phototrophic bacterium Rhodobacter sphaeroides, initially by inactivation of the high-affinity terminal respiratory oxidase, cytochrome cbb(3). We propose that the O(2)-dependent form allows for the biosynthesis of a low level of bacteriochlorophyll under oxic conditions, so that a rapid initiation of photosynthetic processes is possible for this bacterium upon a reduction of oxygen tension.